Antiinflammatory and Antioxidant Activities of Trifolium resupinatum var. microcephalum Extracts - SABUDAK, T.; DOKMECI, D.; OZYIGIT, F.; ISIK, E.; AYDOGDU, N. (Asian Journal of Chemistry, 2010)
The antiinflammatory and antioxidant activities of the ethanol extract of Trifolium resupinatum L. var. microcephalum (Leguminosae) have been assessed on arthritic rats. The extract (1.35 and 13.5 mg/kg, i.p.) significantly reduced the paw edema induced by the complete Freund's adjuvant. Furthermore, it also inhibited lipid peroxidation. These effects of T. resupinatum extract may be directly linked to the content in triterpene saponins and flavonoid compounds and consequently to their free radical scavenging activities.